The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3389/fphar.2021.773722
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of the Cecal Microbiome and Plasma Metabolomics to Explore NaoMaiTong and Its Potential Role in Changing the Intestinal Flora and Their Metabolites in Ischemic Stroke

Abstract: Ischemic stroke (IS), as a leading cause of disability worldwide, affects intestinal bacterial communities and their metabolites, while recent discoveries have highlighted the importance of the intestinal microflora in the development of IS. Systematic investigations of complex intestinal bacterial communities and their metabolites during ischemic brain injury contribute to elucidate the promising therapeutic targets for IS. However, the associations between intestinal microbiota and related circulating metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 88 publications
0
20
0
Order By: Relevance
“…Regulate intestinal microorganisms and microbial metabolites, inhibiting Enterobacteriaceae to repair the intestinal barrier and promote the prognosis of stroke 1. SD rat (44) Improve the prognosis of IS…”
Section: Naomaitongmentioning
confidence: 99%
See 3 more Smart Citations
“…Regulate intestinal microorganisms and microbial metabolites, inhibiting Enterobacteriaceae to repair the intestinal barrier and promote the prognosis of stroke 1. SD rat (44) Improve the prognosis of IS…”
Section: Naomaitongmentioning
confidence: 99%
“…In addition, decoctions, including Pueraria root and rhizome, ameliorated dyslipidemia, elevated blood viscosity, and a high risk of thrombosis after stroke and repaired the ecological imbalance of the gut microbiome and the integrity of the brain-gut barrier (162). NaoMaiTong corrected the dismal prognosis following stroke by restoring gut flora (44). Formulations of Xingu Chengqi stimulate the release of anti-inflammatory factors, such as IL-10, and downregulate proinflammatory factors, Frontiers in Immunology frontiersin.org such as TNF-a, IL-17A, and IL-22 (163).…”
Section: Traditional Chinese Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the development of measures to lower the prevalence of IS and its detrimental consequences is highly warranted. Recent research has demonstrated that the gut microbiota regulates the pathogenesis of IS via the microbiota-gut-brain axis (MGBA) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%